Comparison of the Charges of 10 Selected Surgeries in Imam Reza Hospital with their Official Global Prices - Hosein Ebrahimipour; Elahe Pourahmadi; Shapour Badiee Aval; Alireza Rezazadeh (Gonabad University of Medical Sciences, 2020)
Background: This descriptive, analytic study aimed to compare the costs of 10 types of Global Budget Payment System (GBPS) surgery in Imam Reza Hospital, Mashhad City, Iran, in 2016 with the prices in the GBPS.  Methods: From hospital-discharge data and patients' bills, we identified 10 types of GBPS surgeries performed in Imam Reza hospital. The patients were grouped according to the surgical procedures performed in the 10 GBPS category. Data on hospital charges and cost-to-charge ratios were used to assess charges and costs for specific resources, as well as for the hospitalization overall. The researcher received training from the experts in the field of hospital accounting to learn how to determine the charge of GBPS surgeries.  Results: The results showed that in some surgeries such as hysterectomy, natural delivery, C-section, tonsillectomy, hernia repair, and appendectomy, charges of services were higher than their average prices GBPS and in arteriovenous anastomosis surgery, cholecystectomy, tympanoplasty, and thyroidectomy were lower than average prices GBPS. One of the main goals of Iran's Ministry of Health in developing GBPS was to provide a unified framework for managing admission and treatment costs in state-owned hospitals. The obtained data were analyzed by the Wilcoxon signed-rank test and the independent samples t test with 0.05 statistical significance. The results of this study and similar works show that most hospitals have completely neglected this aspect of GBPS.  Conclusion: A fact that is reflected in the wide-ranging variations in the charge of GBPS surgeries in different hospitals despite their being paid based on the same rates and guidelines.